Preparation and Characterization of Anti-CeTNT-1 and Anti-CeTNT-4 Antibodies (Bangladesh Journal of Scientific and Industrial Research, 2010)
Among the four CeTNT isoforms, CeTNT-1, CeTNT-2 are body wall types, CeTNT-4 is pharynx type and CeTNT-3 is expressed in both the body wall and pharyngeal tissue. In our previous study, we used body wall and pharynx type anti-CeTNI, anti-CeTNC and anti-CeTM antibodies to observe the tissue specific interaction of the TNI isoforms with others TN subunits and tropomyosin isoforms. To extent the interaction study of CeTNT isoforms, in this study, we prepared and characterized the body wall type anti-CeTNT-1 and pharynx type anti- CeTNT-4 antibodies. For the preparation of the anti-CeTNT-1 and anti-CeTNT-4 antibodies, in this study we constructed the pCTNT-1 and pCTNT-4 expression vectors. The sub-cloned of the pCTNT-1 and pCTNT-4 expression vectors were verified by DNA sequencing. These expression vectors were used to generate fusion proteins of the body wall, TNT-1 and pharyngeal TNT-4 isoforms in Escherichia Ecoli. The expression of these fusion proteins were confirmed by SDS-PAGE analysis. The anti-CeTNT-1 and anti-CeTNT-4 antibodies were prepared in the rabbit by using the gel cut of the CeTNT-1 and CeTNT-4 fusion proteins. The antibody specificity of the CeTNT-1 and CeTNT-4 fusion proteins was also judged by Western-analysis using prepared anti-CeTNT-1 and anti-CeTNT-4 antibodies. The antibody specificity results indicated that anti-sera against each of both the body wall type TNT-1 and pharynx type TNT-4 isoforms had tissue specificity. Key words: Troponin T, Caenorhabditis elegans, Body wall, Pharynx DOI: 10.3329/bjsir.v44i3.4413 Bangladesh J. Sci. Ind. Res. 44(3), 371-376, 2009